2017
DOI: 10.1007/s11606-017-4123-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of and reasons for electronic cigarette use in primary care patients

Abstract: Over half of smokers in primary care have ever used e-cigarettes, and one-fifth are currently using them. Most reported using e-cigarettes to cut down or quit cigarettes. Primary care providers should be prepared to discuss e-cigarettes with patients. Screening for e-cigarette use may help identify and treat patients interested in changing their cigarette smoking habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
3
13
1
Order By: Relevance
“…Previous studies have shown that e‐cigarette users tend to have higher rates of conventional cigarette use, and our work supports this assertion on a national level. McQueen et al specifically examined 110 patients with head and neck cancer and a smoking history and demonstrated that non–e‐cigarette users achieved higher quit rates than e‐cigarette users.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that e‐cigarette users tend to have higher rates of conventional cigarette use, and our work supports this assertion on a national level. McQueen et al specifically examined 110 patients with head and neck cancer and a smoking history and demonstrated that non–e‐cigarette users achieved higher quit rates than e‐cigarette users.…”
Section: Discussionsupporting
confidence: 89%
“…8 education tried e-cigarettes previously. Few studies have compared current and former e-cigarette users, 5,19 but studies comparing these groups can be helpful in identifying factors potentially associated with persistent e-cigarette use.…”
Section: P-value (Vs Current Use)mentioning
confidence: 99%
“…The finding that the majority of current e-cigarette users in this study reported the reason for using e-cigarettes was to quit smoking cigarettes is consistent with other clinical populations of smokers. 5 It is important that providers caring for newly diagnosed cancer patients are aware of the high prevalence of and reasons for e-cigarette use among smokers, as patients may come to their providers with questions about these products. 20 Patients should be advised of the unknown long-term health risks of e-cigarettes and their unknown efficacy for smoking cessation.…”
Section: T a B L E 3 Behavioral Physical And Psychological Charactementioning
confidence: 99%
See 1 more Smart Citation
“…T he study by Kalkhoran et al 1 uses data from a smokingcessation trial to describe e-cigarette use among primary care patients. The study participants were recruited from patients in three primary care practices in San Francisco who were enrolled in a test of a tablet-based intervention.…”
mentioning
confidence: 99%